2010
DOI: 10.1002/jbmr.224
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cadmium exposure and the association with bone mineral density and fractures in a population-based study among women

Abstract: All people are exposed to cadmium (Cd) via food; smokers are additionally exposed. High Cd exposure is associated with severe bone damage, but the public health impact in relation to osteoporosis and fractures at low environmental exposure remains to be clarified. Within the population-based Swedish Mammography Cohort, we assessed urinary Cd [U-Cd, mg/g of creatinine (cr)] as a marker of lifetime exposure and bone mineral density (BMD) by dual-energy X-ray absorptiometry (DXA) among 2688 women. Register-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 32 publications
6
90
0
Order By: Relevance
“…[25] For this reason it is recommended that supplementing the diet of postmenopausal women with calcium is effective in preventing height and bone loss to avoid public health impact of decreased calcium especially in Asian women. [24] In this study there was an obvious increase in serum levels of cadmium and lead in osteoporotic patients compared to controls; this agrees with previous studies done in Asia [26][27][28] , Europe [5,[29][30] , and America . These results were independent of tobacco smoking, which is both an important source of Cadmium and a risk factor for osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[25] For this reason it is recommended that supplementing the diet of postmenopausal women with calcium is effective in preventing height and bone loss to avoid public health impact of decreased calcium especially in Asian women. [24] In this study there was an obvious increase in serum levels of cadmium and lead in osteoporotic patients compared to controls; this agrees with previous studies done in Asia [26][27][28] , Europe [5,[29][30] , and America . These results were independent of tobacco smoking, which is both an important source of Cadmium and a risk factor for osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
“…These results were independent of tobacco smoking, which is both an important source of Cadmium and a risk factor for osteoporosis. [30] Several studies tried to clarify the mechanisms for Cadmium-induced osteoporosis. Experimental data demonstrate a direct effect of Cadmium on bone both ways: with decreased bone formation and increased bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental exposure to lead in the elderly has been associated with cognitive decline (Bandeen-Roche et al 2009;Grashow et al 2013;Nordberg et al 2000;Power et al 2014;Shih et al 2006;van Wijngaarden et al 2011), impaired motor skills (Grashow et al 2013), increased blood pressure (Perlstein et al 2007), ischemic heart disease (Jain et al 2007), decreased renal function (Tsaih et al 2004), falls and fractures in women (Khalil et al 2008), hearing loss (Park et al 2010) and vision problems (Schaumberg et al 2004;Wu et al 2014). Cadmium, for which fewer studies have been conducted in the elderly, has also been associated with an increased risk of atherosclerotic plaques (Fagerberg et al 2012), peripheral artery disease (Tellez-Plaza et al 2013a), osteoporosis (Engstrom et al 2011;Gallagher et al 2008) and macular degeneration (Shiue 2013;Wu et al 2014). In addition, a decrease in muscle mass and muscle strength, which are components of frailty (Cesari et al 2006), might also contribute to the observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence supports the contribution of environmental lead and cadmium to the development of several age-related chronic diseases, including cardiovascular disease (Navas-Acien et al 2007;Tellez-Plaza et al 2013b), chronic kidney disease (Navas-Acien et al 2009), and osteoporosis (Engstrom et al 2011;Gallagher et al 2008;Khalil et al 2008). Despite this evidence, and the established connection between these diseases and the frailty syndrome (Heuberger 2011), no previous studies have examined the association between lead or cadmium exposure and frailty.…”
Section: Introductionmentioning
confidence: 99%
“…Other published studies showed effects on bone at low-level exposure to environmental cadmium (Gallagher, Kovach & Meliker, 2008;Schutte et al, 2008;Wu, Magnus & Hentz, 2010;Nawrot et al, 2010;Thomas et al, 2011;Engström et al, 2011Engström et al, , 2012, although some did not find positive associations (Rignell-Hydbom et al, 2009;Trzcinka-Ochocka et al, 2010).…”
Section: Recent Studiesmentioning
confidence: 95%